Digital Signature Implementation as a New Smart Governance Model - Budiarti, Nursani; Putra, Yahya Pandega; Nurmandi, Achmad (Society, 2020)
With the times, nothing is impossible with internet technology. One of the advantages of the internet is that it allows for developing it to support creativity and openness to the public, especially ICT-based governance or smart governance, by implementing digital signature, both in public services implementation and in correspondence and other documents. Most of the previous digital signature studies were limited to technical research on digital signature’ patterns and design. This study aims to describe digital signature implementation as a new smart governance model. This study uses a qualitative research method and data sources consisting of reference data from various previous studies and data sourced from national online media news. Based on the analysis results using NVivo 12 Plus software, digital signature implementation is needed to anticipate cybercrime threats in effective, efficient, and accountable public services implementation as a new smart governance model.